2008
DOI: 10.1002/clen.200700160
|View full text |Cite
|
Sign up to set email alerts
|

Waste Activated Sludge Disintegration in an Ultrasonic Batch Reactor

Abstract: The production of excess sludge is one of the most serious challenges in biological wastewater treatment. In the present work, disintegration is added as a new additional unit operation in a wastewater treatment plant, and the main objective is to reduce the amount of excess sludge. The use of high power ultrasound can effectively disintegrate the bacterial cells, and thereby, enhance the subsequent biodegradation during digestion. In the study, attempts are made to determine the disintegration capacity of was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
(24 reference statements)
2
10
0
Order By: Relevance
“…These observations are in high contrast to the claims formulated by Feng et al (2009), who postulated that the ammonia nitrogen concentration of the supernatant rapidly increased with increasing energy input as a direct consequence of the ultrasonic sludge disintegration. The results are, however, confirmed by Khanal et al (2006), Bougrier et al (2005) and Akin (2008), who claim that the ammonium release is a secondary phenomenon due to biological hydrolysis of the released organic nitrogen. The rate of hydrolysis is dependent on the electron donor available, or rather the oxygen concentration in the activated sludge.…”
Section: Correlation Check Of the Y-matrixsupporting
confidence: 75%
“…These observations are in high contrast to the claims formulated by Feng et al (2009), who postulated that the ammonia nitrogen concentration of the supernatant rapidly increased with increasing energy input as a direct consequence of the ultrasonic sludge disintegration. The results are, however, confirmed by Khanal et al (2006), Bougrier et al (2005) and Akin (2008), who claim that the ammonium release is a secondary phenomenon due to biological hydrolysis of the released organic nitrogen. The rate of hydrolysis is dependent on the electron donor available, or rather the oxygen concentration in the activated sludge.…”
Section: Correlation Check Of the Y-matrixsupporting
confidence: 75%
“…However, increase in the TS content from 0.5% to 2.0% resulted in a significant decrease in the DD COD because of the reduction of ultrasonic energy per unit amount of solid matters in the sludge. Similar to our study, Akin () and Huan et al . () reported that the higher the concentration of the sludge, the harder it is to disintegrate.…”
Section: Resultssupporting
confidence: 93%
“…; Zhang et al . ; Akin ). However, the modelling of ultrasonic sludge disintegration had been scarcely studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…This rapid disintegration achieved in the first 2.5 min was likely resulted from the rapid cavitational effect arising from the collapse of powerful transient bubbles generated in fractions of microseconds close to microbial cells [21]. In addition, sonication at higher densities in shorter periods was determined as a more effective alternative for US sludge pretreatment [22,23]. Therefore, these outcomes suggested that US pretreatment could be performed in periods shorter than 2.5 min to reduce both capital and operating costs of the pretreatment process.…”
Section: The Effect Of Sonication On Sludge Disintegrationmentioning
confidence: 99%